The Morning Star in Semba Scarves as a Source of Ideas For Creating Batik Motifs for Casual Wear - Firdaus, Roihatal Jannati; Sudarwanto, Aan (Runtas : Journal Of Arts And Culture, 2023)
This Final Project entitled "The Morning Star in Semba Scarves as a Source of Ideas For Creating Batik Motifs for Casual Wear". The source of the idea that forms the basis for the creation of works is the weaving craft of the NTT region, especially the Ende region, namely Selendang Semba. On the Semba scarf there is a Morning Star motif which as a unique character so that the creators want to make it an idea for creating batik motifs. The purpose of creating this final project is to apply the Morning Star motif found in the Semba scarf into casual clothing for young women aged 17 year sand over. The methods used in making this work are expression, technique and creation. The process of making batik designs using the strongest character-taking technique found in the semba shawl becomes a batik motif. The making of the batik works uses the written batik process followed by the coloring process in the form of dyed caps with artificial dyes, namely napthol and remashol. The material in the work uses primissima cloth, atype of princess dance, whichhasa smooth character, dense fibers, easily absorbs sweat so it is comfortable when used as casual clothing. The output of this Final Project is in the form of 4 works of women's casual clothing, a fashion catalog, a teaser for the final work process and as cientificarticle. This work is titled "Abhita" and has different titles in each of his works, the clothes are titled : Asha, Sachi, Trisha, Agni.